THE ANALYSIS OF HADITS HERMENEUTICS BASED ON MUSTAFA AL-SIBA’I'S PERSPECTIVE - Hidayatus Sholihah; Ahmad Zaenurrosyid; Sarjuni Sarjuni (Kopertais Wilayah X Jawa Tengah, 2023)
Mustafa Al-Siba’i is a warrior figure for the authenticity of Hadith. After Muhammad, as messenger of God, passed away, some orientalists have emerged who doubt the authenticity of the Hadith. Then Mustafa is one of the figures at the forefront of countering the orientalists who are trying to make Muslims doubt the authenticity of Hadits. This article aims to analyze how Hadith Hermeneutics in the perspective of Mustafa Al-Siba’i. Therefore, who is the figure of Al-Siba’i, what is his educational background and his works will be discussed, before analyzing his thoughts related to the authenticity of the Hadith to find out the style of his thinking. The method applied was library research or reviewing various existing literature, mainly sourced from various journals and books explore about Mustafa Al-Siba’i's thoughts. The results of the study of various literatures explain that Al-Siba’i is an extraordinary scholar and preacher who actively writes and produces various logical, systematic and monumental works. He has written various works to counter the efforts of orientalists or liberal figures to weaken the Muslim community's belief in Hadith. Al-Siba’i's works can influence Muslims to the authenticity of Hadith as Islamic law or the second reference for Muslims after the Qur'an.